Pelaksanaan Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Bagi Anak Cerebral Palsy Kelas V.d Di SLB YPPLB Padang (Deskriptif- Kualitatif) - Anggi Arisandi (Universitas Negeri Padang, 2014)
ABSTRACT: Implementation of Sport and Physical Education Learning Health For Cerebral Palsy Children Class Vd in SLB YPPLB Padang . ( Descriptive - qualitative ) Department Thesis PLB FIP Padang State University . The approach used is descriptive qualitative data collection techniques using observation , interviews , and Documentation Studies . This study aims to look at the objective in nature and control of the treatment is not required because the study was not intended to test a specific hypothesis but simply describe what the symptoms are observed . Therefore, the researcher wants to describe the Learning Implementation of Physical Education Sport and Health For Cerebral Palsy Children's Class Vd SLB YPPLB In Padang . Based out of eight times ( 8X ) existing field notes , researchers have not seen the special learning programs in Sports Physical Education and Health Education for Children Cerebral Palsykelas Vd , As well as learning as distinguished from other students who have the ability / disability is different . It is also justified by the teacher of Physical Education Sport and Health initials ZL , he said that there is no specialization in learning activities Physical Education Sport and Health For Cerebral Palsy Children it. Additionally Sport and Physical Education teacher health can also overcome the obstacles faced when learning takes place in the classroom / field . Kata Kunci : Pelaksanaan Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Bagi Anak Cerebral Palsy Kelas V.d Di SLB YPPLB Padang